2018
DOI: 10.1111/ijsa.12223
|View full text |Cite
|
Sign up to set email alerts
|

A large sample investigation of the presence of nonlinear personality‐job performance relationships

Abstract: We examine 123 data sets from validation studies of a single five‐factor model‐based occupational personality measure for evidence of curvilinear relationships with job performance. Research has produced discrepant findings about whether and when to expect curvilinear relationships between normal range personality measures and job performance. Previous studies have relied on small and unsystematic sampling, a variety of noncomparable performance criteria, the use of personality inventories for which construct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 59 publications
3
15
5
Order By: Relevance
“…However, some authors of these studies have failed to replicate these findings (Le et al, 2011, second sample) or found a different pattern (LaHuis et al, 2005, second sample), and other researchers have found no evidence for meaningful curvilinearity (Nickel, Roberts, & Chernyshenko, 2019;Robie & Ryan, 1999;Walmsley, Sackett, & Nichols, 2018;Whetzel, McDaniel, Yost, & Kim, 2010). The differences could be due to several varying features across studies, but here we highlight analytic approaches.…”
Section: The Nomological Link Between Mental Disorders and Job Performentioning
confidence: 79%
“…However, some authors of these studies have failed to replicate these findings (Le et al, 2011, second sample) or found a different pattern (LaHuis et al, 2005, second sample), and other researchers have found no evidence for meaningful curvilinearity (Nickel, Roberts, & Chernyshenko, 2019;Robie & Ryan, 1999;Walmsley, Sackett, & Nichols, 2018;Whetzel, McDaniel, Yost, & Kim, 2010). The differences could be due to several varying features across studies, but here we highlight analytic approaches.…”
Section: The Nomological Link Between Mental Disorders and Job Performentioning
confidence: 79%
“…Robie and Ryan (1999) found no evidence of nonlinearity for conscientiousness-job performance relations (five samples). Walmsley (2013;Walmsley, Sackett, & Nichols, 2018) examined 123 validity studies and reported a "general lack of meaningful curvilinear effects for each Big Five scale in relation to overall job performance" (p. ii). For conscientiousness, the quadratic term provided only small incremental validity over the linear term for overall-, intrapersonal-, interpersonal-, leadership-, and work skill performance (ΔR 2 was .034, .032, .032, .027, and .031, respectively).…”
Section: The I-o Psychology Perspectivementioning
confidence: 99%
“…The relationship between personality scores and job performance is important because this determines how personality assessment scores can be utilized in personnel selection (Converse & Oswald, 2014;Walmsley, 2013). Prediction of job performance:…”
Section: Nonlinear Relationship Between Personality Assessment Scormentioning
confidence: 99%
“…The relationship between personality scores and job performance is important because this determines how personality assessment scores can be utilized in personnel selection (Converse & Oswald, ; Walmsley, ). Considering that few research examined faking under nonlinear relationships between personality scores and job performance together with faking in personality assessments, questions such as ‘What is the impact of faking in a personality assessment on the prediction of job performance under a nonlinear relationship, compared to findings in literature when a linear relationship was assumed?’ ‘Are consequences of selection substantially affected by faking under a nonlinear relationship?’ and ‘Can the adverse impact of faking on consequences in selection decisions be alleviated if a selection approach considering a nonlinear relationship is employed?’ may arise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation